Some Algebraic Properties of the Wilson Loop - Han Li; M. Nadeem; M. A. Ali; H. Mutee ur Rehman (Journal of Mathematics)
In this article, some algebraic properties of the Wilson loop have been investigated in a broad manner. These properties include identities, autotopisms, and implications. We use some equivalent conditions to study the behavior of holomorphism of this loop. Under the shadow of this holomorphism, we are able to observe coincident loops.